Sistem Informasi Administrasi Kelompok Kerja Guru Pendidikan Agama Islam Kecamatan Gerokgak Berbasis Web - Firda Safitri (Jurnal Ilmiah Informatika, 2019)
Working Group of Teachers of Islamic Religious Education State Elementary School Gerokgak District is an organization engaged in Islamic Religious Education, where the board and its members consist of special Islamic Education Teachers (GPAI) both civil servant teachers and non-civil servants who are responsible and participate in promoting Islamic Education and fight for the rights of students who are Muslim. KKGPAI-SDN Gerokgak District has been established since 20 years ago. During this time KKGPAI-SDN has a desire to memanjukan KKGPAI-SDN Gerokgak District not only in terms of activities, but in terms of administration that is still very manual done using Ms.Word and Ms. Exel, such as in making activity reports covering the results of the contest, filing of GPAI for UAS, UTS, UKK and USBN, financial reports, monthly routine reports of teaching and learning activities GPAI, and archiving correspondence in all aspects, making KKGPAI take a long time to completing the results of the contest to be informed to the school in the sub-district Gerokgak, data collection of funds and the expenditures that will be reported by the secretary to the chairman of the KKG, filing letters and questions made KKGPAI-SDN team compilers, reports on teaching and learning activities to be reported to the Office The Ministry of Religion of Buleleng Regency as a monthly fixed report for KKGPAI and GPAI every month as a means of assessing the District-level KKG and GPAI in advancing its vision and mission. Data collection methods carried out are through observation or field observation, interwiew or interview and literature study. The software development method used is the waterfall method through 5 stages, namely, the analysis stage, the design stage, the coding stage, the testing phase and the maintenance phase. From the explanation and the results of the discussion above can be concluded that the Administrative Information System Working Group Teachers Islamic Religious Education Gerokgak District was designed using PHP and MySQL programming language as one form of efforts to improve the quality Teacher Working Group Administration in District Gerokgak.